Entrepreneurial leadership and green product development for grand challenges: the roles of strategic sensitivity, collaborative innovation capability and political skill - Zahoor, Nadia; Khalid, Adeel; Usman, Muhammad; Yasin, Naveed (Taylor & Francis, 2026)
Green product development provides firms with a pathway to address grand challenges, including climate change, which threaten ecological balance, economic stability, and social well-being. Drawing on the dynamic capability view, this study examines how entrepreneurial leadership enables green product development in resource-constrained economies. We propose that strategic sensitivity and collaborative innovation capability mediate this relationship, while leaders’ political skill moderates the effect of entrepreneurial leadership on strategic sensitivity. Using survey data from 252 SME leaders in Pakistan and analysing the model using structural equation modelling, the findings support the proposed hypotheses. Specifically, entrepreneurial leadership positively contributes to green product development. Also, strategic sensitivity and collaborative innovation capability significantly mediate the relationship between entrepreneurial leadership and green product development, while political skill strengthens the positive effect of entrepreneurial leadership on strategic sensitivity. This study contributes to the literature on entrepreneurial leadership, dynamic capabilities, and green product development, offering insights into how firms in resource-constrained settings can leverage leadership capabilities to create sustainable solutions and address grand societal challenges.
Keywords: Grand societal challenges; entrepreneurial leadership; green product development; strategic sensitivity; political skills; dynamic capability; fi=InnoLab|en=InnoLab|